The analysis of training and development of reserve components in efforts to strengthen the national defense system against global military threats (qualitative) - Sudarya, Agus (Technium Social Sciences Journal, 2021)
The various types of military and non-military threats which occur in the world globally indirectly demand the readiness of every country to deal with them. The form of the military threats which happened frequently in the global world are war and territorial disputes between countries. In this case, implicitly and explicitly, Indonesia is also facing military threats related to sovereignty, one of which is the dispute over the South China Sea which has now changed its name to the North Natuna Sea. In terms of maritime military defense, Indonesia itself relies on the presence of the naval forces from the Navy and Bakamla (Navy Security Agency), but this defense effort has not yet involved all levels of society. The state defense system owned by Indonesia is the Universal Defense System which involves the strength of the main Component, the reserve components, and the supporting components. The reserve component is a group of people who are fostered and trained on a military basis to prepare strength when faced with a military emergency situation. In the process of training and developing the reserve components, the competent authorities have prepared the basics and provisions in maximizing the potential of their human resources. The aims of the research were to find out how the training and development of the reserve component in an effort to strengthen the national defense system. The method of the research was using qualitative method with literature study as the collecting data method. The result of the research is that it is hoped that there will be a transfer of knowledge system in the process of training and developing human resources for Indonesian reserve components, in order to strengthen the national defense system against global military threats.